(In)Sensitivity to Accuracy? Children’s and Adults’ Decisions About Who to Trust: The Teacher or the Internet - Guerrero, Silvia; Sebastián-Enesco, Carla; Morales, Irene; Varea, Elena; Enesco, Ileana (Frontiers in Psychology, 2020)
Recent research has challenged the extended idea that when presented with conflicting information provided by different sources, children, as do adults, make epistemic judgments based on the past accuracy of each source. Instead, individuals may use relatively simple, but adaptive non-epistemic strategies. Here we examined how primary-school children (N = 114) and undergraduate students (N = 57) deal with conflicting information provided by two key sources of information in their day-to-day lives: their teacher and the Internet. In order to study whether the inaccuracy of a source generated a decline in trust, we manipulated this variable between participants: teacher-wrong and Internet-wrong conditions. For this, we first presented two baseline trials, followed by the accuracy manipulation, and finally, two post-test trials. Analyses were performed on group performance as well as on individual performance, to explore the individual patterns of responses. Results revealed that most participants showed no preference for any source during baseline, with no age differences in their overall choices. Crucially, when a given source provided inaccurate information about a familiar issue, most children and adults did not lose trust on this source. We propose tentative explanations for these findings considering potential differences in the participants’ strategies to approach the task, whether or not epistemic.